2011
DOI: 10.1002/mus.21948
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical delay in biceps brachii assessed by ultrafast ultrasonography

Abstract: Using ultrasound we tested the utility of determining the relative contribution of the main muscle structures/mechanisms to the electromechanical delay in the biceps brachii. Nine subjects underwent electrically evoked contractions with the echographic probe maintained over the muscle and the myotendinous junction. No difference was found between the onset of muscle fascicle motion (Dm, 5.57 ± 1.37 ms) and the onset of myotendinous junction motion (Dt, 5.47 ± 1.38 ms), whereas significant differences were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 6 publications
4
37
0
Order By: Relevance
“…Using very high frame rate ultrasound, the present study demonstrates that the delay between electrical stimulation and onset of muscle fascicle shortening (Dm) is not different in DMD patients compared with healthy controls. As this delay is principally attributed to synaptic transmission and excitation-contraction coupling (15,26), this result suggests that the efficiency of the excitation-contraction coupling might be affected independently of its duration. This is in line with a previous animal study showing that the time to release the maximal quantity of Ca 2ϩ is not affected (Ϸ4 ms; Ref.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Using very high frame rate ultrasound, the present study demonstrates that the delay between electrical stimulation and onset of muscle fascicle shortening (Dm) is not different in DMD patients compared with healthy controls. As this delay is principally attributed to synaptic transmission and excitation-contraction coupling (15,26), this result suggests that the efficiency of the excitation-contraction coupling might be affected independently of its duration. This is in line with a previous animal study showing that the time to release the maximal quantity of Ca 2ϩ is not affected (Ϸ4 ms; Ref.…”
Section: Discussionmentioning
confidence: 92%
“…As previously described in Lacourpaille et al (18,19), the detection of the onset of both muscle fascicle motion and external force production was defined visually. We defined the EMD as the time lag between the onset of the electrical stimulation (i.e., artifact of stimulation) and the onset of force production (15,18,19,26). Then delays between the onset of electrical stimulation and the onset of muscle fascicle motion (Dm) and between the onset of fascicle motion and the onset of force production (Tm) were calculated (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It reflects both electro-chemical processes (i.e., synaptic transmission, propagation of the action potential, excitation-contraction coupling) as well as mechanical processes (i.e., force transmission along the active and the passive part of the series elastic component, SEC) [1]. The relative contributions of both electro-chemical and mechanical processes involved in EMD has recently been characterized on gastrocnemius medialis [2] and biceps brachii [3], [4] using very high frame rate ultrasound. More precisely, the delay between the muscle electrical stimulation and the onset of muscle fascicles motion has been mainly attributed to electro-chemical processes and the delay between the onset of fascicles motion and the onset of both the myotendinous junction motion and the force production has been attributed to mechanical processes [2], [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…The relative contributions of both electro-chemical and mechanical processes involved in EMD has recently been characterized on gastrocnemius medialis [2] and biceps brachii [3], [4] using very high frame rate ultrasound. More precisely, the delay between the muscle electrical stimulation and the onset of muscle fascicles motion has been mainly attributed to electro-chemical processes and the delay between the onset of fascicles motion and the onset of both the myotendinous junction motion and the force production has been attributed to mechanical processes [2], [3], [4]. While the study of gastrocnemius medialis reported a delay of about 2.4 ms between the onset of muscle fascicles motion and the onset of myotendinous junction motion (i.e., the delay to transmit force along the aponeurosis) [2], fascicles and myotendinous junction motion occurred concomitantly in biceps brachii [3], [4].…”
Section: Introductionmentioning
confidence: 99%